Squamous cell carcinoma developing in a huge dermoid cyst of the ovary in an 80-year-old woman - case report - (:unkn) unknown (I R O G CANADA, INC, 2007)
A case of an 80-year-old patient with squamous cell carcinoma originating from a huge septated dermoid cyst of the right ovary is reported. There were bilateral dermoids in the patient. The tumor sizes were 30 x 40 x 20 cm and 4 x 3 x 5 cm in the right and left ovary, respectively, confirmed by ultrasound and computed tomography. Squamous cell carcinoma arose in the solid part of a huge dermoid cyst of the left ovary. Total abdominal hysterectomy and bilateral salpingo-oophorectomy, omentectomy and appendectomy were performed. The tumor was confined to the right ovary. The patient was categorized as FIGO Stage IA. She recovered uneventfully and there was no evidence of recurrence in the early-stage case during one year of follow-up. The clinical and pathological features, treatment modalities and prognosis of squamous cell carcinoma are described.
Keywords: dermoid cyst; squamous cell carcinoma; prognosis; MALIGNANT-TRANSFORMATION; TERATOMA; BENIGN; DEGENERATION; INSITU